Effect of Position and Connected Atom on Photophysical and Photochemical Properties of Some Fluorinated Metallophthalocyanines - Saglam, Ozgul; Farajzadeh, Nazli; Yasa Atmaca, Goknur; Erdogmus, Ali; Kocak, Makbule Burkut (WILEY, 2021)
This study presents the preparation of a new phthalonitrile derivative namely 3-(4-(trifluoromethoxy)thiophenoxy)phthalonitrile (1) and a series of its metallated phthalocyanines (M = Zn (II) (1a) and In(III) (1b)). In addition, the peripheral analog of the indium phthalocyanine chloride (2b) was newly synthesized. Characterization of the resulting compounds was carried out by utilizing various spectroscopic methods such as FT-IR,H-1 NMR and UV-Vis spectroscopy. The influence of concentration on aggregation properties of compound1awas investigated at different concentrations of DMSO. The effect of solvent type on aggregation properties of compound1awas studied, as well. According to the referred procedures, the macrocyclic molecules (2a,3a-band4a-b) were prepared. The effect of some parameters including metal ion, the position of the substituent and the connected atom (oxo or thio) on photochemical and photophysical features of compounds (1a-b,2a-b,3a-b, and4a-b) was studied for evaluation of their potential as a photosensitizer in PDT, comparatively. The highest singlet oxygen quantum yields (phi(Delta) = 0.71 for1aand 0.80 for2b) were obtained for complexes1aand1bin DMSO. The photophysical and photochemical features of the studied macromolecules are therefore suitable for photodynamic therapy applications.
Keywords: PHTHALOCYANINES BEARING CHLORO; SUBSTITUTED PHTHALOCYANINES; ANTIOXIDANT PROPERTIES; AGGREGATION; ZINC; ELECTROCHEMISTRY; DERIVATIVES; SEPARATION; GALLIUM; Biochemistry & Molecular Biology; Biophysics